Investigation of Astaxanthin Effect on Cisplatin Ototoxicity in Rats by Using Otoacoustic Emission, Total Antioxidant Capacity, and Histopathological Methods - AKAKIN, DİLEK; ÖZBEYLİ, DİLEK (SAGE PUBLICATIONS INC, 2021)
Background: Cisplatin-induced ototoxicity is related to oxidative stress. Astaxanthin is one of the most powerful antioxidants in nature. Aims/objectives: To investigate the protective effect of astaxanthin on cisplatin-induced ototoxicity. Materials and Methods: Thirty-five Sprague Dawley female rats were divided into 5 groups: control, cisplatin, and cisplatin with 10, 20, and 40 mg/kg astaxanthin groups. Cisplatin group received a single intraperitoneal injection of 14 mg/kg cisplatin. While saline was administered in the control group, in the other 3 groups, 10, 20, and 40 mg/kg daily doses of astaxanthin were administered through orogastric cannula before administration of cisplatin. Baseline and 10th day otoacoustic emission tests were administered. An intracardiac blood sample was taken to measure total antioxidant capacity (TAC), and the cochleas of the animals were investigated histopathologically. Results: Hearing level of astaxanthin 40 mg/kg + cisplatin group was higher at 24 kHz and 32 kHz frequencies compared to the cisplatin group. The TAC value of the cisplatin group was lower than both the control and astaxanthin + cisplatin groups (P< .05). On histopathological examination, the other groups were deformed compared to the control group, but no statistically significant difference was observed between the astaxanthin + cisplatin and cisplatin groups. Conclusions and significance: Astaxanthin showed protective effect at high frequencies when it was administered at high dose. Thus, astaxanthin may have protective effect against cisplatin-induced ototoxicity.
Keywords: astaxanthin; cisplatin; ototoxicity; total antioxidant capacity; PROTECTION; MECHANISMS